profile
Опубликовано - 4 месяца назад | По предмету Математика | автор Аноним

3(4x-9)+4(2x+3y)-5(6x-2y) При x=2 y =-1

  1. Ответ
    Ответ дан Борисова Анастасия
    Если х = 2 и у = - 1, тогда 3 * (4x - 9) + 4 * (2x + 3y) - 5 * (6x - 2y) = 3 * (4 * 2 - 9) + 4 * (2 * 2 + 3 * (- 1)) - 5 * (6 * 2 - 2 * (- 1)) = 3 * (8 - 9) + 4 * (4 + (- 3)) - 5 * (12 - (- 2)) = 3 * (- 1) + 4 * (4 - 3) - 5 * (12 + 2) = - 3 + 4 * 1 - 5 * 14 = - 3 + 4 - 70 = 1 - 70 = - 69;
    0



Топ пользователи


Hekady (
206)
shozavitya (
180)
znanija (
172)
Eveline (
58)